x2 + 6x - (a2 + 2a - 8) = 0 by using quadratic formula.
Answers
Answered by
4
Answer:
hence roots are obtained.
Attachments:
![](https://hi-static.z-dn.net/files/d82/99f88661497a12c04da556232888db82.jpg)
Answered by
10
x²+6x-(a²+2a-8)=0
=> x²+6x-(a²+4a-2a-8)=0
=> x²+6x-[a(a+4)-2(a+4)]=0
=> x²+6x-(a+4)(a-2)=0
Splitting the middle term,we get
=>x²+(a+4)x-(a-2)x-(a+4)(a-2)=0
=> x[x+(a+4)]-(a-2)[x+(a+4)]=0
=> [x+(a+4)][x-(a-2)]=0
=> x+(a+4)=0 Or x-(a-2)=0
=> x = -(a+4) Or x = (a-2)
Therefore,
x = -(a+4) Or x = (a-2)
hey mate i hope this will help you
=> x²+6x-(a²+4a-2a-8)=0
=> x²+6x-[a(a+4)-2(a+4)]=0
=> x²+6x-(a+4)(a-2)=0
Splitting the middle term,we get
=>x²+(a+4)x-(a-2)x-(a+4)(a-2)=0
=> x[x+(a+4)]-(a-2)[x+(a+4)]=0
=> [x+(a+4)][x-(a-2)]=0
=> x+(a+4)=0 Or x-(a-2)=0
=> x = -(a+4) Or x = (a-2)
Therefore,
x = -(a+4) Or x = (a-2)
hey mate i hope this will help you
Similar questions